Повышение энергоэкономической эффективности тяговой сети переменного тока - Мыцко, Р. С. (НТУ "ХПИ", 2007)
In the article compared system of hauling supply of alternating current with screening and strengthening send-offs that system of hauling supply with transformers. It is rotined that at application of the system with screening and strengthening send-offs expenses diminish both on capital building and on exploitation.
Keywords: электрификация железных дорог; тяговые подстанции; контактная сеть; тяговая сеть; тяговое электроснабжение; отсасывающие трансформаторы